COCCIDIOSIS OF DOMESTIC PIGEONS (COLUMBA LIVIA DOMESTICA) - K. Senthilvel; K. Madhavan Pillai (Journal of Veterinary and Animal Sciences, 1995)
Coccidiosis in pigeon due to Eimeria columbae and Eimeria labbeana is reported